FORMULATION AND EVALUATION OF CLOBETASOL-17-PROPIONATE-LOADED CARBOXYMETHYL CHITOSAN NANOPARTICLE - YADAV, MAMTA; AGGARWAL, PANKAJ; YADAV, DEEPIKA; SINGH, ANAND (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Formulation and evaluation of clobetasol-17-propionate-loaded carboxymethyl chitosan nanoparticle. Psoriasis is a chronic skin disorder caused due to the autoimmune factors. It has a detrimental psychological and physiological impact on patients due to the emergence of apparent skin. The systemic therapy with anti-psoriatic drugs such corticosteroids, immunosuppressant, and gene suppressors causes severe side effects. As a result, increasing the effectiveness and safety of the aforementioned medicines when applied topically would be extremely useful in avoiding the side effects associated with the systemic route of administration. Methods: Chitosan (CS) has not been widely used in the clinic applications but due to its limited solubility and poor mechanical characteristics. CS, on the other hand, is chemically changed to form carboxymethyl (CMC), which is soluble at both neutral and basic pH. Chemical modifications can also be used to attach different functional groups and control hydrophobic, cationic, and anionic properties. CMC is a promising carrier that might possibly traverse the thick scales of psoriatic skin since it is a penetration enhancer that allows drug diffusion through either the transcellular or paracellular pathways. Comparative study is done using CMC as a polymer and CD as a polymer. Results: CP-loaded CMC nanoparticles show better result results than CP-loaded CD polymer. Conclusion: Clobetasol-17-propionate-loaded carboxymethyl chitosan nanoparticle shows better results with improved solubility.